Investigation of premenstrual syndrome in connection with physical activity, perceived stress level, and mental status—a cross-sectional study - Dózsa-Juhász, Olívia; Makai, Alexandra; Prémusz, Viktória; Ács, Pongrác; Hock, Márta (Frontiers in Public Health, 2023)
Introduction The premenstrual syndrome (PMS) is a critical factor in women’s health, which, in addition to physical inactivity, can be influenced by the body mass index (BMI), stress, and mental state, among others. The study aimed to assess the severity of PMS symptoms among young women regarding physical inactivity, BMI, mental state, and perceived stress level. Methods A total of 198 female participants between the ages of 18–45 took part in a 6-month cross-sectional online questionnaire study. The average age of the participants was 25.37 ± 4.80 years. To assess physical activity, stress, mental state, and premenstrual symptoms, we employed standard questionnaires, including the International Physical Activity Questionnaire-Short Form (IPAQ-SF), the Perceived Stress Scale (PSS), the General Health Questionnaire-12 (GHQ-12), and the Premenstrual Assessment Form-Short Form (PAF-SF). The collected data were analyzed using IBM SPSS (Statistical Package for Social Sciences) version 28.0 software, with a significance level set at p < 0.05. Results During the analysis, we observed a significant relationship (p = 0.020) between regular exercise and the severity of PMS symptoms, as well as between mental state and PMS symptoms (p < 0.001). Furthermore, our findings revealed a significant negative correlation between regular physical activity and perceived stress levels (r = −0.179; p = 0.012), as well as between regular exercise and the participants’ mental state (r = −0.157; p = 0.027). Additionally, we identified a significant difference (p < 0.001) among the six subgroups formed based on the PAF-SF and average PSS questionnaire results. Moreover, a significant difference was observed between the PAF-SF case and control groups in terms of BMI averages (p = 0.019). Discussion The research findings indicate that the severity of PMS symptoms is influenced by regular physical activity, mental state, and stress.